Analisis Kesulitan Belajar pada Anak dengan Gangguan Perkembangan Peserta Didik pada SMP Negeri 20 Surabaya - Atta Yusli Salsabil; Daliah Salsabila; Hardiyanti, Diva Aprinita; Nabila, Ika Malika; Wulandari, Mey (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
With a mixed research methods, data is collected through in-depth interviews questionnaire questions, direct observation and documentation studies. Research subjects included 9th grade students, guidance and counseling teachers, and homeroom teachers. The research results show that the learning difficulties faced by students are related to challenges in understanding the material, low ability to concentrate, and limitations in social interaction. Contributing factors include students' personal conditions, teachers' lack of understanding of students' special needs, and limited supporting facilities at school. This research also identified several strategies implemented by teachers, such as individual learning, game-based approaches, and strengthening communication with parents. All of these efforts aim to support the student learning process optimally. In conclusion, more intensive collaboration between schools, teachers and parents is needed to create a learning environment that is inclusive and responsive to the needs of students with developmental disorders, so that they can develop optimally in learning in accordance with the principles of the Independent Curriculum.